Arquitectura mudéjar en la región del valle del Alto Cauca, Colombia (siglo XVIII): tipos y técnicas (2019)
Two of the finest examples of Moorish architecture that arose in the Nueva Granada´s territory (now Colombia), they are still standing in the region of Alto Cauca valley: the first is San Francisco´s tower, Cali, dating from 1772? Which is an important monument of the late American Mudejar. The second is the tower attached to the chapel of El Salado village, in the same region, also of the eighteenth century and which there are no documents to reconstruct its historical genesis. In both cases highlights the management of the brick in sight as a building material, confirming the fact that one of the protagonists of Moorish architecture in America will undoubtedly be the builder. It arise some questions that this paper will attempt to resolve in a very short and specific way: what body of knowledge must make use ofa eighteenth century´s mason from Nueva Granadato materialize examples like those?, Where did he get raw materials (mainly clays and limes)?, what was his main contribution to the architecture of the region where he thrived?